Penguatan Literasi Informasi Siswa di Sekolah Islam Terpadu: Studi Kasus di SMP IT Budi Mulia Padang - Pitriani, Anita; Asyuri, M. Rafly; Safitri, Puspa (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to examine strategies for strengthening students' information literacy at SMP IT Budi Mulia Padang through the role of the library and school librarians. The study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation to obtain a realistic picture of the conditions in the field. The results of the study show that students' interest in reading is still relatively low, due to time constraints and the lack of appeal of the reading collections available in the library. Librarians have attempted to improve information literacy through various strategies, such as collaborating with the Library Office, implementing a 15-minute daily reading program, collaborating with teachers in learning, utilizing digital technology, and creating a comfortable, attractive, and educational reading space. However, the effectiveness of the programs implemented still faces a number of challenges, particularly in terms of sustainability and active student involvement. Therefore, more integrated, innovative, and sustainable strategies are needed so that libraries can function optimally as centers for information literacy development and support the improvement of reading culture in the school environment.